The kinetochore module Okp1CENP‐Q/Ame1CENP‐U is a reader for N‐terminal modifications on the centromeric histone Cse4CENP‐A. (2nd November 2018) - Anedchenko, Ekaterina A; Samel‐Pommerencke, Anke; Tran Nguyen, Tra My; Shahnejat‐Bushehri, Sara; Pöpsel, Juliane; Lauster, Daniel; Herrmann, Andreas; Rappsilber, Juri; Cuomo, Alessandro; Bonaldi, Tiziana; Ehrenhofer‐Murray, Ann E
Abstract: Kinetochores are supramolecular assemblies that link centromeres to microtubules for sister chromatid segregation in mitosis. For this, the inner kinetochore CCAN/Ctf19 complex binds to centromeric chromatin containing the histone variant CENP‐A, but whether the interaction of kinetochore components to centromeric nucleosomes is regulated by posttranslational modifications is unknown. Here, we investigated how methylation of arginine 37 (R37Me) and acetylation of lysine 49 (K49Ac) on the CENP‐A homolog Cse4 from Saccharomyces cerevisiae regulate molecular interactions at the inner kinetochore. Importantly, we found that the Cse4 N‐terminus binds with high affinity to the Ctf19 complex subassembly Okp1/Ame1 (CENP‐Q/CENP‐U in higher eukaryotes), and that this interaction is inhibited by R37Me and K49Ac modification on Cse4. In vivo defects in cse4‐R37A were suppressed by mutations in OKP1 and AME1, and biochemical analysis of a mutant version of Okp1 showed increased affinity for Cse4. Altogether, our results demonstrate that the Okp1/Ame1 heterodimer is a reader module for posttranslational modifications on Cse4, thereby targeting the yeast CCAN complex to centromeric chromatin. Synopsis: The conserved inner kinetochore proteins Okp1 and Ame1 are directly targeted to the centromeric histone H3 variant Cse4 in budding yeast, functioning as readers for post‐translational modifications in its N‐terminal tail. Saccharomyces cerevisiae Cse4 CENP‐A carries R37 methylation (R37Me) and K49 acetylation (K49Ac) in its extended N‐terminal domain. The Cse4 N‐terminus (Cse4N) interacts with Okp1 CENP‐Q /Ame1 CENP‐U, components of the Ctf19/CCAN kinetochore complex. R37Me and K49Ac in Cse4N reduce the interaction between Cse4N and Okp1/Ame1. Mutations in OKP1 and AME1 suppress the centromeric defects caused by mutation of Cse4‐R37, and increase the binding affinity of Okp1/Ame1 to Cse4N. Abstract : Inhibition of kinetochore protein targeting by arginine 37 methylation and lysine 49 acetylation of the budding yeast H3 variant Cse4 extends the epigenetic histone code concept to centromere specification.